A latent class analysis of food hygiene and handling practices among urban and peri-urban residents in Hyderabad, India. (March 2021) - Lagerkvist, Carl Johan; Hatab, Assem Abu; Nedumaran, Swamikannu; Ravula, Padmaja
Abstract: In developing countries, food-borne diseases, attributable to lack of, or inappropriate, food hygiene and handling practices at home, are expected to increase due to a rapid growth in the consumption of fats and animal source foods. The context-specific and situational practices corresponding to underlying traits of food hygiene and handling practices for home-cooked food were investigated for a set of 662 randomly selected households in Hyderabad, India. Results indicate that about one-third of the households lack access to a refrigerator. Of those with a refrigerator, a majority (83%) had the temperature set at medium, with an actual temperature ranging from 8 to 11 °C. Results also show that smell, followed by food appearance rather than taste or labelled expiry dates were used as the main criteria for edibility. Furthermore, six indicators related to handling, storage and cooking non-vegetarian food and three indicators related to storage of the cooked food were assessed. For households with a refrigerator, the latent class analysis identified three exclusive and exhaustive subgroups of households representing the heterogeneity of handling and hygiene traits, while two subgroups were identified for households not having a refrigerator. Only a small proportion of households (12.6%) with a refrigerator were profiled as having adequate and consistent practices. Remaining subgroups revealed substantial within-group variations in terms of consistency in certain behaviors. Next, latent class modelling with covariates related to socio-demographic, socio-economic, socio-spatial variables and health or dietary outcomes showed that having higher than a primary school education, having a high percentage of food expenditure, or non-optimal refrigerator temperature were predictive of the latent class with more adequate practices. For households without a refrigerator, five covariates related to social class, age, income, and obesity distinguished the latent classes. These findings of latent trait-specific behaviors have implications for actions aiming to inform and direct behavioral change interventions on food safety practices in the developing countries. Highlights: We examined food handling and hygiene at home for 662 households in Hyderabad, India. Socio-economic characteristics explained lack of refrigeration. Smell, followed by food appearance were used as the main criteria for edibility. Safer practices were adopted by only 12% of the sample. Education and food expenditure were predictive of latent traits.